Abundance [compact disc, unabridged] : the future is better than you think - Diamandis, Peter H. (Tantor Media, 2012)
Providing abundance is humanity's grandest challenge. This is a book about how people rise to meet that challenge. Abundance establishes hard targets for change and lays out a strategic road map for governments, industry, and entrepreneurs, giving people plenty of reason for optimism.